If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.80x + 0.80(120) = 0.40(142) Multiply 0.80 * 120 0.80x + 96 = 0.40(142) Reorder the terms: 96 + 0.80x = 0.40(142) Multiply 0.40 * 142 96 + 0.80x = 56.8 Solving 96 + 0.80x = 56.8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + 0.80x = 56.8 + -96 Combine like terms: 96 + -96 = 0 0 + 0.80x = 56.8 + -96 0.80x = 56.8 + -96 Combine like terms: 56.8 + -96 = -39.2 0.80x = -39.2 Divide each side by '0.80'. x = -49 Simplifying x = -49
| 13(t-3)+5=6(3t+4)-10 | | 2.3x-4.25=3.3x+2.15 | | 0.80x+0.80(120)=0.40(120) | | 4x+2=14-3x | | 0.7(x+20)+0.1x=30 | | 9.8*sin(30)= | | -2+0= | | m=4m+4u | | 7(x-6)+5=-37 | | -3x+2=1x-2 | | 4x^2(x-6)+6x(x-6)=0 | | 46=-5x+11 | | 3.6x+39.3=9.5-11.3x | | R-RVZt= | | x-3.2=5.7 | | x-2.1=6.3 | | 2(4x-4)+1=x | | 32x+x^2=256 | | t=R-Rvz | | -2x-7=x+1 | | 1/4x=-5/4 | | x^2+4y=2(3x-6-x)+x^2 | | 3(-5)-9=2(-5)+1 | | Y=-4(1)-1 | | .600x-3.9x-4.9x=0 | | (x+4)(2x-1)=11 | | x^3-x^2-2.75=0 | | -3x+7=5x+15 | | 8x/6x^2-6x | | 63=p-0.25p | | 8+2n-6=8n+6-5n | | -.600x+3.9x+4.9x=0 |